Aortic root volume is associated with contained rupture of the aortic annulus in balloon‐expandable transcatheter aortic valve replacement. Issue 4 (26th October 2015) - Reinöhl, Jochen; Psyrakis, Dimitrios; Kaier, Klaus; Kodirov, Sodikdjon; Siepe, Matthias; Gutmann, Anja; von zur Mühlen, Constantin; Moser, Martin; Ahrens, Ingo; Pache, Gregor; Zirlik, Andreas; Langer, Mathias; et al.
Abstract : Background: Aortic annulus rupture is a rare, but potentially fatal complication of transcatheter aortic valve replacement (TAVR), especially when it occurs by balloon‐expandable devices. In order to improve the predictability of procedures and avoid ruptures we investigated whether or not the aortic root volume measures is a useful indicator of risk, and if it could be useful for the prosthesis size selection. Methods and Results: From a retrospective series of 172 TAVR patients, seven experienced contained aortic annulus ruptures. The receiver operating curves were used to illustrate sensitivity and specificity of the different aortic annulus size and aortic root volume measures. The annulus area oversizing of ≥20% resulted in a sensitivity of 100%, specificity of 55.76%, and positive predictive value (PPV) of 8.75%. In patients receiving 26mm prostheses, the aortic root volume (ARV <13600mm 3 ) provided a better specificity and PPV (79.63 and 18.52%, respectively). A two‐step testing procedure considering the area derived average annulus diameter ( D area <23mm) as a first separating parameter and then the ARV (<13, 600mm 3 ) as a further indicator showed the most promising results with the PPV of 31.25%. Regardless of the procedure steps no false negative results were predicted. Conclusions: Our data show that the ARV provides a better predictive value for correct prosthesis sizing than established annulus measurements, especially in 'borderline' annuli. We suggest a two‐step testing procedure for prostheses size selection, considering D area and ARV to minimize the risk of annulus rupture. Prospective studies and examination of larger datasets are warranted to confirm these findings. © 2015 Wiley Periodicals, Inc.